Nurses' Perceptions of Their Practice Following a Redesign Initiative. Issue 4 (October 2020) - Thomas, Lily; White, Jane; Scanlon, Kerri
Abstract : A significant number of quantitative studies have associated a positive or healthy work environment with job satisfaction. Nurses, patients, and organizational characteristics have been studied as contributing factors. Other studies have focused on structural or physical environmental factors such as noise, space, or lighting as influencing to satisfaction. Little research has focused on how a changed work environment initiated by an organization for improved patient care affected the nurses' perceptions of how their practice had changed. The purpose of this qualitative study was to determine nurses' perceptions of a changed work environment on their practice, specifically patient care. Twelve nurses participated in the semistructured interviews. Interviews were transcribed verbatim and content analysis was used to identify categories of phrases and the resulting major themes. Most importantly, and the significant overall theme of patient- and family-centered improved care described their perceptions of this change. Other themes included camaraderie, nurse-patient relationships, being valued by the organization, and efficiency for decreasing stress. The results illuminate and extend some of the findings from prior quantitative studies on professional practice environments. A major contribution of this research is the perception of the nurses, often overlooked in quantitative studies. Significant was the nurses' view that the changed environment improved patient- and family-centered care although, as in other study findings, there was a view that peer camaraderie decreased.